Pengembangan Multimedia Pembelajaran pada Materi Sistem Ekskresi Manusia Mata Pelajaran IPA Kelas VIII SMP - Afifah, Nurul; Syafril, Syafril; Yeni J, Fetri; Yusri, Meldi Ade Kurnia (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research aims to develop multimedia learning that can help students to understand the process of the human excretory system and can facilitate students to learn independently. This type of research is research and development (R&D) with a 4-D development model. The results of the study obtained that the average validity score by material experts was 4.85 with the category of